2024
DOI: 10.3390/plants13060876
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping for Bacterial Wilt Resistance and Plant Height in Tomatoes

Muhammad Irfan Siddique,
Emily Silverman,
Frank Louws
et al.

Abstract: Bacterial wilt (BW) of tomatoes, caused by Ralstonia solanacearum, is a devastating disease that results in large annual yield losses worldwide. Management of BW of tomatoes is difficult due to the soil-borne nature of the pathogen. One of the best ways to mitigate the losses is through breeding for disease resistance. Moreover, plant height (PH) is a crucial element related to plant architecture, which determines nutrient management and mechanical harvesting in tomatoes. An intraspecific F2 segregating popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…In tomato, numerous studies have been conducted to map resistant QTLs against bacterial wilt. These studies have identified QTLs associated with bacterial wilt resistance on chromosomes 1, 2, 3, 4, 6, 7, 8, 10, and 12 with different R 2 value [10][11][12]. Notably, the QTLs on chromosomes 6 and 12 have been consistently detected under varying environmental conditions, using different mapping materials, and employing different inoculation methods, thus confirming their status as major QTLs [12,13].…”
Section: Introductionmentioning
confidence: 69%
“…In tomato, numerous studies have been conducted to map resistant QTLs against bacterial wilt. These studies have identified QTLs associated with bacterial wilt resistance on chromosomes 1, 2, 3, 4, 6, 7, 8, 10, and 12 with different R 2 value [10][11][12]. Notably, the QTLs on chromosomes 6 and 12 have been consistently detected under varying environmental conditions, using different mapping materials, and employing different inoculation methods, thus confirming their status as major QTLs [12,13].…”
Section: Introductionmentioning
confidence: 69%